The Legend: King Jaja of Opobo - Orefuja, Temitope (Literamed Publications (Nig.) Limited, 2009)
A boy was born into the house of certain couple in 1821. He was later captured by slave trader and sold into slavery. He rose to become a vibrant business man and king. The book gives a lucid account of the journey of King Jaja of Opobo from the early stages of his life till he became king over a town he developed.
Keywords: Biography & Autobiography; Juvenile Nonfiction